Advances in mechanical engineering, materials and mechanics : selected contributions from the 7th International Conference on Advances in Mechanical Engineering and Mechanics, ICAMEM 2019, December 16-18, 2019, Hammamet, Tunisia /: selected contributions from the 7th International Conference on Advances in Mechanical Engineering and Mechanics, ICAMEM 2019, December 16-18, 2019, Hammamet, Tunisia. ([2020]) - Unknown
No abstract available